The velocity of the fluid due to the many-sphere Oseen hydrodynamic interactions - Pieńkowska, I. (Archives of Mechanics, 1997)
We consider the velocity field, generated in the incompressible, viscous fluid due to the hydrodynamic interactions between a finite number of solid spheres. The particular properties of the velocity field, due to the convective inertia of the fluid, are examined. The inertia effects are taken into account up to the contributions of the order of 0(Re).